(untitled) (Journal of the Bangladesh Agricultural University, 2019)
This study assessed the value chain of shea in Niger State, Nigeria. One hundred and forty respondents were selected through a multistage random technique. Data were analyzed using value addition method and descriptive statistics. Findings revealed that there are four key players in the shea value chain, namely the sole picker, the processor/picker, butter marketer and the retailer. Regarding value addition, it was found that the sole picker adds a value of ₦250 (3.10%), the local processor, adds a value of ₦1550 (19.38%), the shea butter marketer adds ₦600 (7.70%) and the retailer adds a value of ₦5600 (70%). Furthermore, findings revealed that the retailer has the highest margin of ₦3460 (70.47%) while the processor has a margin of ₦1050 (21.38%). The sole picker has the lowest margin of ₦150 among players in the chain. However, findings reveal that, the picker has a higher margin when he doubles as a processor. Since majority of the pickers and processors are women, empowerment of the female gender can be enhanced through interventions in the shea value chain. Therefore, this study recommends a gender-based study of the shea value chain in the study area which will further reveal potentialities for empowering women and the household in the study area. Furthermore, to give leverage to the sole picker in terms of the size of market margin attracted, it may be expedient to empower the sole picker to get involved in the processing of the nuts. J Bangladesh Agril Univ 17(3): 369–374, 2019